Association of Malassezia pachydermatis with the otitic and the normal ear canal of the dogs - BOURTZI-HATZOPOULOU (Ε. ΜΠΟΥΡΤΖΗ-ΧΑΤΖΟΠΟΥΛΟΥ) E.; PETRIDOU (Ε. ΠΕΤΡΙΔΟΥ) E.; PSYHOYOS (B. ΨΥΧΟΓΙΟΣ) V. (Journal of the Hellenic Veterinary Medical Society, 2017)
The purpose of this study was to investigate the presence of M. pachydermatis in otitic and healthy ear canals of the dogs and to test the sensitivity of this microorganism to antifungal agents. A total of 180 swabs, 98 from otitic and 82 from clinically healthy dogs, were collected during the years 1998-2000 in Thessaloniki area (Greece). From all the swabs, smears for direct microscopic examination and inoculation on selective media for bacteria and fungi isolation were made. From the 90 M. pachydermatis isolates, 68 (69,38%) were made from infected and 32 (39,02%) from clinically healthy dogs. M. pachydermatiswas the sole isolate in 20 (20,39%) infected and in 12 (14,63%) non infected dogs. In 48 otitic and in 20 clinically healthy dogs, M. pachydermatis was associated with bacteria as Staphylococcus spp., Pseudomonas spp., Proteus spp. and Streptococcus spp. and fungi as Candida spp. ana Aspergillus spp.. S. intermediuswas isolated from 13 infected and 20 non infected animals. A mixed bacterial flora was grown from 6 infected and 22 clinically healthy animals, respectively, while no growth of microorganisms from 11 otitic and 8 healthy dogs was observed. All Malassezia tested strains (46) were found sensitive to ketoconazole, econazole, miconazole and clotrimazole. Nystatin was found effective to 38 isolates and non effective to 8.